Administrative and Legal Status of the National Police of Ukraine as a Subject of State Policy Implementation in Human Rights and Freedoms - A. V. Tanko (Law and Safety)
The article is focused on studying the phenomenon of the administrative and legal status of the National Police as a subject of Ukrainian state policy implementation in human rights and freedoms. The author outlines the essence and content of the administrative and legal status of the National Police of Ukraine through the leading categories of "law" and "freedom", which are important for the democratic processes developing in Ukrainian society.